Axial compression response of foam concrete infilled light gauge profiled steel composite wall panels - Prabha, P.; Ambily, P.S; Saravanan, M. (Journal of Structural Engineering, 2024)
Composite wall, a novel form of construction with profiled steel sheets as the facing material with an infill concrete intended for use as partition and shear walls in steel framed buildings has the potential to be used as structural elements in load bearing construction. The axial compression behaviour of two such composite walls of size (1m × 3m) and 130 mm thick utilizing profiled cold formed steel sheets of 0.8 mm thick and foam concrete of density 850 kg/m3 is studied by conducting experiments. The interaction between sheet and concrete is achieved by using through-through mild steel studs. Brittle foam concrete gained enough ductility by the steel facing and also enhances the local buckling capacity of thin steel sheet. The number of studs and their spacing are sufficient enough to cause the failure of wall panel by yielding of steel sheets rather than buckling, which is the design criteria. Composite wall panels showed gradual load-displacement behaviour up to the failure load and exhibited ductile deflections in the post-peak behaviour by sustaining almost 30% of the failure load due to the confinement action of steel sheet and the studs. The composite wall panel exhibited higher load carrying capacities and ductile deflections than conventional systems and has the potential to act as load bearing wall for G+3 buildings.